Prognostic Significance of End-Stage Liver Diseases, Respiratory Tract Infection, and Chronic Kidney Diseases in Symptomatic Acute Hepatitis E - Fan, Huahao; Fan, Junfen; Chen, Suming; Chen, Yangzhen; Gao, Huiru; Shan, Liying; Li, Xue; Gu, Fengjun; Zhuang, Hui; Sun, Lijun (Frontiers in Cellular and Infection Microbiology, 2021)
Symptomatic hepatitis E virus (HEV) infection is sporadic, and usually occurs in a limited number of infected patients, which hinders the investigation of risk factors for clinical outcomes in patients with acute HEV infection. A retrospective cohort study enrolling 1913 patients with symptomatic acute hepatitis E in Beijing 302 Hospital from January 1, 2001 to December 31, 2018 was conducted. The baseline characteristics, clinical features and laboratory data of these HEV infection cases were analyzed. ALB, PLT, ALT, T-BiL, INR and SCR levels, along with the MELD score, hospitalization days, co-morbidity number and mortality were taken as major parameters for comparing the clinical manifestations in our study. We found that not all pre-existing chronic liver diseases exacerbate clinical manifestations of acute hepatitis E. Among all of the comorbidities, end-stage liver diseases (ESLDs, including ascites, cirrhosis, hepatic coma, hepatorenal syndrome and hepatic failure), respiratory tract infection and chronic kidney diseases (CKDs, including renal insufficiency and renal failure) were found to remarkably increase the mortality of patients with symptomatic HEV infection. Furthermore, the severity evaluation indexes (SEI), such as MELD score, duration of hospital stay, and co-morbidity number in HEV patients with underlying comorbidities were much worse than that of their counterparts without relevant comorbidities.